Identitas dan Integrasi Sosial: Studi Kasus Budaya Nyadran Masyarakat Lokal di Dusun Krecek Desa Getas Kecamatan Kaloran Kabupaten Temanggung - Vina Fellinda Alfiatun Maghfiroh (Jurnal Dirosah Islamiyah, 2024)
This study discusses identity and social integration, a case study of local community nyadran culture in Krecek Hamlet, Getas Village, Kaloran District, Temanggung Regency. Through descriptive qualitative methods based on trend analysis techniques, which involve studying past records related to social structure, lifestyle and culture. This research aims to understand identity and how the social and cultural integration of Nyadran is established. The research subjects were the people of Krecek Hamlet, Getas Village, Kaloran District, Temanggung Regency. The research results obtained are that Nyadran Culture is an integral part of the identity and social integration of Buddhist communities, referring to traditions that go beyond mere rituals to form strong social relationships. It was revealed that the importance of Nyadran Culture is in promoting values such as mutual cooperation, unity, tolerance, religion and cooperation, as well as maintaining harmony between religious community groups. This cultural adaptation of nyadran contributes to the formation of overall social integration in various types of religion.